2017
DOI: 10.1177/0267659117706014
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of acute normolvolemic hemodilution and autologous prime on intraoperative blood management during cardiac surgery

Abstract: Regression results show that the use of ANH will result in the greatest decline in hematocrit values. When combined with AP, higher hematocrits and lower transfusions were seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 46 publications
0
23
0
2
Order By: Relevance
“…It has been reported that the use of autologous priming of the extracorporeal circuit prior to CPB may reduce intraoperative transfusion of RBC. 47,48 This technique is extremely attractive as a blood management tool, but requires that the entire cardiac team be involved to see it successfully applied. When examining its use in the present study, we saw a greater than two-fold use in the DN group as opposed to both other CP techniques (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the use of autologous priming of the extracorporeal circuit prior to CPB may reduce intraoperative transfusion of RBC. 47,48 This technique is extremely attractive as a blood management tool, but requires that the entire cardiac team be involved to see it successfully applied. When examining its use in the present study, we saw a greater than two-fold use in the DN group as opposed to both other CP techniques (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the priming a At least one of the following factors which affect fluid balance was not taken into account or documented: type and/or dosage of cardioplegia used, the mean arterial blood pressure target during CPB, the use of autotransfusion, the use of hemofiltration, intraoperative blood loss, and the patients' weight/length/body mass index, and/or the transfusion trigger. 26 Nanjappa et al 27 Ševerdija et al 24 Stammers et al 28 Trapp et al 18 Vandewiele et al 29 1 26 Nanjappa et al 27 Ševerdija et al 24 Stammers et al 28 Trapp et al 18 Vandewiele et al 29 10 At least one of the following factors which affect fluid balance were not taken into account or documented: type and/or dosage of cardioplegia used, the mean arterial blood pressure target during CPB, the use of autotransfusion, the use of hemofiltration, intraoperative blood loss, and the patients' weight/length/body mass index, and/or the transfusion trigger. volumes in the RAP groups were significantly higher in the studies that concluded RAP was not beneficial in terms of lowering blood transfusions (Mann-Whitney U test, median priming volume in RAP groups 1,131 vs. 748 mL, p = 0.036).…”
Section: Individual Studiesmentioning
confidence: 99%
“…Kearsey et al 26 Nanjappa et al 27 Ševerdija et al 24 Stammers et al 28 Trapp et al 18 Vandewiele et al 29 1 groups. Moreover, it is possible that patient management strategies in these three studies did not allow for using lower priming volumes, resulting in the inability to find a significant difference in blood transfusion rate between the RAP and control groups.…”
Section: Itemmentioning
confidence: 99%
See 2 more Smart Citations